Does government data openness have a green effect? an examination from the perspective of green innovation - Wang, Jingyuan; Chen, Yan; Luo, Qingfeng (Frontiers in Environmental Science, 2025)
Firms’ green R&D and innovation directly impact the national economy’s green and high-quality development. However, data resources play a significant role in altering traditional development models and promoting sustainable economic growth. Government data openness (GDO) offers a vital opportunity for the widespread transmission of data value. Existing literature has not yet examined whether GDO can intrinsically affect the green R&D and innovation of micro-level firms. In this study, we examine the impact of GDO on corporate green innovation using data from A-share industrial listed companies in China spanning 2007–2022 and employing the difference-in-differences (DID) method. The results indicate that GDO significantly promotes corporate green innovation. Mechanism tests reveal that GDO fosters corporate green innovation through channels such as enhancing corporate risk-taking, alleviating financing constraints, and optimizing the business environment. Further examination shows that improvements in the quality of GDO significantly enhance corporate green innovation. Moreover, the green effect of GDO is comprehensive and does not vary with the classification of green innovation types. According to the heterogeneity analysis, when management’s green cognition is higher, the firm is younger, environmental regulations are more stringent, and intellectual property is less protected, the green effect of GDO is more noticeable. This paper provides insights for promoting high-quality GDO, advancing green innovation and development in emerging market countries.